Career Plateau Forms Turnover Intention: The Important Role of Affective Commitment and Career Satisfaction - Noerchoidah, Noerchoidah; Widowati, Dyah; Mahmudah, Siti; Pudji Estiasih, Soffia (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
The pervasive high employee turnover intention, particularly prevalent in the hospitality sector, often disrupts company operations. This study investigates the influence of career plateau on turnover intention, mediated by affective commitment and career satisfaction. The research population comprises all hotel employees in East Java, with a sample size of 170 employees. The data analysis used the Partial-Least-Square Structural-Equation-Modeling (PLS-SEM) approach. The hypothesis testing results substantiate that career plateau significantly and negatively impacts affective commitment and career satisfaction. Furthermore, both affective commitment and career satisfaction significantly and negatively influence turnover intention. The study also reveals that career plateau significantly and positively affects turnover intention when mediated by affective commitment. However, when judged by career satisfaction, the career plateau's effect on turnover intention was positive but insignificant.